Grieving Widows’ Lived Experiences In A Rural South African Setting - Motsoeneng, Molefi; Modise, Motalenyane, Alfred. (Journal of Psychology in Africa, 2020 Vol. 30, No. 3, 264–267, 2020)
The study explored widows’ social isolation and the stigma experienced in a rural South Africa setting Participants were a purposive sample of 10 widows (black = 95%; age range 30 to 60 years old) The widows completed semi-structured individual interviews on their sense of community Thematic analysis indicated that widows self-perceived as a social burden to extended family and to experience a deep sense of social isolation and loneliness, dealing with their grief and loss The widows reported to lack in social support after the death of their partners and to be treated to humiliating cultural stereotypes Implied guilt by the in-laws and other family members about the widows’ involvement in the death of their partners is a recurrent influence in the widowhood experience in a South African rural setting.
Article
Keywords: Loneliness and humiliation; Perceived social burden; Rural; Widows